Control of two-spotted spider mite, Tetranychus urticae Koch (Acari: Tetranychidae) by predators on potted plants (University Journal of Zoology, Rajshahi University, 2009)
Three predators Scolothrips sexmaculatus Pergande, Phytoseiulus persimilis Athias - Henriot and Stethorus punctillum Weise were used to control two-spotted spider mite, Tetranychus urticae Koch on potted bean plants. Mite population increased exponentially on the untreated plants, but on the predator treated plants, increase of mite population was checked and remained within minimum number. Early release of predator checked the mite population earlier and kept it lower than on late released plants. All the three predators may be used as bio-control agents against two-spotted spider mite. Key words: Control, Tetranychus urticae, Scolothrips sexmaculatus, Phytoseiulus persimilis, Stethorus punctillum and bio-control agents. Â  doi:10.3329/ujzru.v27i0.1954 Univ. j. zool. Rajshahi Univ. Vol. 27, 2008 pp. 51-54